Inflammatory Biomarkers and Liver Histopathology in Non-Uremic and Uremic Chronic Hepatitis C Patients - Bengu Tatar; Sukran Kose; Emel Pala; Erhan Tatar (Acta Medica, 2017)
Background: The aim of this study is to investigate the association between hepatic activity index (HAI) and fibrosis score (FS) with inflammation biomarkers in non-uremic and uremic hepatitis C positive patients. Methods: Fifty chronic hepatitis C (cHepC) positive patients, having a liver biopsy were included in this study. Liver biopsies were scored according to modified ISHAC scoring system. 25 healthy controls of similar age and gender were also enrolled as control group. Serum YKL-40, neutrophil/lymphocyte ratio (NLR), thrombocyte/lymphocyte ratio (PLR), CRP and Immunoglobulin (IgG, A and M) levels were used to determine inflammation. AST to Platelet Ratio Index (APRI) score was also evaluated. According to biopsy findings patients were divided into 2 groups: low (0–2) and severe (3–6) FS. Results: Patients with cHepC had increased inflammation compared to the healthy controls. End-stage renal disease (ESRD) patients had higher levels of inflammation markers (NLR, IgG, CRP and YKL-40) and lower HCV RNA levels, HAI and FS compared to non-uremic patients. When patients were grouped into 2 according to FS as mild and severe, IgG (p < 0.001), YKL-40 (p = 0.02) levels and APRI score (p = 0.002) were significantly higher compared to mild FS (p = 0.002). YKL-40 levels (t value: 3.48; p = 0.001) and APRI score (t value: 4.57, p < 0.001) were found as independent associated with FS in non-uremic patients. However, in adjusted models, only APRI score (t value: 3.98, p = 0.002) was an independent associated with FS in ESRD patients. Conclusion: In non-uremic cHepC patients, YKL-40 levels and APRI score may be valuable markers of FS. In ESRD patients, there is not sufficient data for prediction of HAI and FS. In these patients, APRI score may provide better information.